Ophiopogonin D improves pancreatic islet cell dedifferentiation to treat diabetes by regulating the GRP78/ROS/PDX1 signaling pathway - Sun, Haoxiang; Tan, Ruixiang; Sun, Yongzhi; Li, Yimeng; Xie, Ying; Zhang, Cheng; Song, Jianping; Zhu, Wei; Zhou, Jiuyao; Deng, Changsheng; Mei, Manxue (Frontiers in Pharmacology, 2025)
IntroductionThe incidence of diabetes is rising annually, significantly impacting public health and imposing a substantial economic burden on society. Ophiopogonin D (Op D) exhibits certain hypoglycemic effects; however, its mechanisms remain unclear.Methodsβ-cell dedifferentiation, distinct from β-cell apoptosis, is a pathogenic mechanism we aim to explore regarding Op D’s regulatory effects. We established an animal model of β-cell dedifferentiation to assess Op D’s impact on glucose tolerance, blood glucose levels, and insulin secretion. We employed immunohistochemistry and immunofluorescence to analyze the expression levels of dedifferentiation-related proteins. Additionally, we created an in vitro β-cell dedifferentiation model using INS-1 cells to evaluate Op D’s influence on insulin secretion and dedifferentiation. Transcriptomic analysis was conducted to explore potential mechanisms by which Op D ameliorates dedifferentiation, with further validation via Western blotting and immunofluorescence. Flow cytometry, fluorescence microscopy, and related assays were used to assess Op D’s effects on oxidative stress. Endoplasmic reticulum (ER) tracing agents marked the ER, and laser confocal microscopy examined ER morphology, with ER stress inducers and inhibitors employed to clarify Op D’s mechanisms.ResultsResults indicated that Op D reduced blood glucose levels, improved glucose tolerance, enhanced insulin secretion, mitigated pancreatic atrophy, and increased PDX1 and FOXO1 expression levels. Furthermore, Op D inhibited ER stress, decreased GRP78 expression, reduced NGN3 levels, elevated PDX1, NKX6.1, and MAFA expression, and decreased oxidative stress-related products (ROS, MDA) while increasing SOD and GSH levels.DiscussionThese findings demonstrate that Op D can improve β-cell dedifferentiation by modulating the GRP78/ROS/PDX1 pathway to inhibit ER stress.